Sampling Characteristics and Calibration of Snorkel Counts to Estimate Stream Fish Populations. (10th November 2014) - Weaver, Daniel M.; Kwak, Thomas J.; Pollock, Kenneth H.
Abstract: Snorkeling is a versatile technique for estimating lotic fish population characteristics; however, few investigators have evaluated its accuracy at population or assemblage levels. We evaluated the accuracy of snorkeling using prepositioned areal electrofishing (PAE) for estimating fish populations in a medium‐sized Appalachian Mountain river during fall 2008 and summer 2009. Strip‐transect snorkel counts were calibrated with PAE counts in identical locations among macrohabitats, fish species or taxa, and seasons. Mean snorkeling efficiency (i.e., the proportion of individuals counted from the true population) among all taxa and seasons was 14.7% (SE, 2.5%), and the highest efficiencies were for River Chub Nocomis micropogon at 21.1% (SE, 5.9%), Central Stoneroller Campostoma anomalum at 20.3% (SE, 9.6%), and darters (Percidae) at 17.1% (SE, 3.7%), whereas efficiencies were lower for shiners ( Notropis spp., Cyprinella spp., Luxilus spp.) at 8.2% (SE, 2.2%) and suckers (Catostomidae) at 6.6% (SE, 3.2%). Macrohabitat type, fish taxon, or sampling season did not significantly explain variance in snorkeling efficiency. Mean snorkeling detection probability (i.e., probability of detecting at least one individual of a taxon) among fish taxa and seasons was 58.4% (SE, 6.1%). We applied the efficiencies from our calibration study to adjust snorkel counts from an intensive snorkeling survey conducted in a nearby reach. Total fish density estimates from strip‐transect counts adjusted for snorkeling efficiency were 7, 288 fish/ha (SE, 1, 564) during summer and 15, 805 fish/ha (SE, 4, 947) during fall. Precision of fish density estimates is influenced by variation in snorkeling efficiency and sample size and may be increased with additional sampling effort. These results demonstrate the sampling properties and utility of snorkeling to characterize lotic fish assemblages with acceptable efficiency and detection probability, less effort, and no mortality, compared with traditional sampling methods. Received April 29, 2014; accepted July 23, 2014